Health needs assessment in patients assisted by a pharmaceutical non-profit charitable organisation: a preliminary pharmacoepidemiological survey based on the analysis of drug dispensation within Italy’s Banco Farmaceutico - Silvia Bini; Antonello E. Rigamonti; Francesco Fiorini; Pietro A. Bertazzi; Gian Francesco Fiorini; Silvano G. Cella (Italian Journal of Medicine, 2015)
We performed a health needs assessment of the vulnerable population cared for by the Banco Farmaceutico, an Italian nonprofit charitable organization that supplies medicines for many centers belonging to different charities. Drugs dispensed in the first half of 2014 by a representative sample of these centers were examined. An independently conducted telephone interview on our centers complemented this data. Adult males and migrants constituted the majority of the user population, and the most dispensed drugs were those for the respiratory system. Of all patients, 40% presented with a chronic problem and more than half needed polypharmacy. Users seek help spontaneously in 70% of the cases, with the centers being able to meet 80% of the existing demand. Patients that could not be managed were referred to local hospitals or collaborating doctors and reasons were explored. We believe our study to be a first attempt to characterise a growing population that is also increasingly represented in emergency departments and internal medicine wards. It is also an evaluation of the quality of data collected by charitable institutions, highlighting a significant need for improvement as they could be the only basis to monitor the health needs of this type of population.